Armenia : Teacher Profile and Policies - World Bank (World Bank, Washington, DC, 2021)
Armenia has made steady progress in reducing poverty in recent years, but development challenges remain, particularly concerning the human development needed to improve the country’s labor productivity. Firms face problems in recruiting and retaining workers with the required skills, and they view the lack of workforce skills as a major obstacle to their activities. The inadequate quality of education, specifically related to practical skills and updated knowledge, has emerged as a key challenge. In addition to technical skills, young Armenians lack generic skills, such as those related to problem solving, critical and creative thinking, teamwork, languages, and leadership (Rutkowski, 2013). Consequently, while employers report skill constraints, a large share of the labor force is unemployed or inactive. Alleviating the skill constraints of Armenia’s firms is crucial to boosting productivity and competitiveness (World Bank, 2017). The objective of this note is to develop a thorough understanding of the profile and practices of teachers in Armenia and to provide evidence-based, actionable policy recommendations for building an effective teaching force. The note incorporates both quantitative and qualitative analyses, drawing on findings from administrative sources, international assessment results and comparative databases, and other studies related to Armenia’s teacher policies. It synthesizes analyses of what teachers’ profiles, priorities, challenges, and practices look like in Armenia, identifies messages for policymakers, and recommends ways to enhance teacher effectiveness and learning for all in Armenia.